A Comprehensive Approach to Power Management in Embedded Systems - Antônio Augusto Fröhlich (International Journal of Distributed Sensor Networks)
Power management is addressed in the context of embedded systems from energy-aware design to energy-efficient implementation. A set of mechanisms specifically conceived for this scenario is proposed, including a power management API defined at the level of user-visible system components, the infrastructure necessary to implement that API (namely, battery monitoring, accounting, autosuspend, and autoresume), an energy-event propagation mechanism based on Petri nets and implemented with aspect-oriented programming techniques, and an autonomous power manager build upon the proposed API and infrastructure. These mechanisms are illustrated and evaluated using realistic wireless sensor network cases that sustain comparisons with other proposals at each of the considered levels. As a result, this paper has its main contribution on the introduction of a comprehensive and systematic way to deal with power management issues in resource-constrained, battery-operated systems.